The Role of Melaleuca alternifolia (Tea Tree) Oil and Casein Polymer Against Pathogenic Staphylococcus aureus and Pseudomonas aeruginosa - Al Naqqash, Zahraa A.E.; Abed, Ibrahim J.; Alsahib, Sanaa A. (Iraqi Journal of Science, 2026)
One of the most dangerous problems facing burn and wound patients is the resistance of bacteria to antibiotics, which requires replacing them with more effective antimicrobial agents such as essential oils. In this study, tea tree oil was used as an antibacterial agent against bacteria from burns and wounds infections such as Staphylococcus aureus and Pseudomonas aeruginosa; polymerizing tea tree oil with casein compound and finding the minimum inhibitory concentration values ​​for the casein polymer agent against the bacteria. The bacteria were isolated and identified using the vitek2 compact system. The sensitivity rates of the bacteria to antibiotics were found through disc agar diffusion and measuring the diameters of inhibition. Minimum inhibitory concentrations were determined using the agar dilution method. The study showed that bacterial isolates numbered 4, 10, 23, 26, 27, and 44 were the most resistant among the S. aureus isolates, while 3, 4, 5, 7, 13, and 14 were the most resistant among the P. aeruginosa isolates. The effect of oil and casein polymer on resistant isolates was tested, and MIC values ​​were obtained, which was 5000 ppm for both types of bacteria, while the MIC ratios of casein polymer varied between 10000 to 20000 ppm for both types of bacteria compared to control.